Porous carbon material with nanosheet shell-coated porous skeleton structure, preparation method and electrode of porous carbon material

The nanosheet-clad porous skeleton structure porous carbon was prepared by molten salt catalytic activation technology, which solved the problem of low pore utilization rate of bulk porous carbon materials, and achieved high specific surface area and excellent capacitance performance.

CN119774609APending Publication Date: 2025-04-08WUHAN UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510016246.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The pore utilization rate of existing bulk porous carbon materials is low, resulting in the mismatch of its electrochemical properties with the high specific surface area, and it is unable to exert excellent performance with high specific surface area.

Method used

The nanosheet shell-clad porous skeleton structure porous carbon was prepared by catalytic activation of molten salt. Through the decomposition, melting and decomposition of the Na2CO3 activator at a certain temperature, the activation environment was designed to prepare porous carbon with special structures.

Benefits of technology

It achieves high specific surface area and high surface utilization, improves the capacitance performance of porous carbon in supercapacitors, and can be used as a high-performance electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774609A_ABST
    Figure CN119774609A_ABST
Patent Text Reader

Abstract

The invention relates to a nanosheet shell-coated porous skeleton structure porous carbon material, a preparation method and an electrode thereof, and the preparation method comprises the following steps: mixing mesocarbon microbeads with a certain proportion of Na2CO3 activator, and treating in an argon atmosphere to obtain the nanosheet shell-coated porous skeleton structure porous carbon. Na2CO3 is adopted as a template agent and an activating agent, the Na2CO3 starts to decompose at the melting point temperature to generate Na2O and CO2 gas, the surplus Na2CO3 can form a molten state, and the molten liquid-phase state guides the carbon microspheres to agglomerate. The temperature is continuously increased, part of Na2CO3 is decomposed to generate Na2O which remains around the aggregate, the Na2O can serve as a template in the aggregate due to the fact that the temperature does not reach the melting point of the Na2O, and the template is removed to form pores; the temperature is increased again to generate CO2 which reacts with the carbon microspheres, and external Na2O further reacts with the gas activation product CO to generate nanosheets which are recombined into a shell; the porous carbon with the nanosheet shell-coated porous framework structure is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of capacitor carbon materials and porous carbon morphology design, and provides a porous carbon material with a nano-sheet shell-encapsulated porous skeleton structure, a preparation method and an electrode thereof. Background Art

[0002] Porous carbon is an important material in the advancement of material science and the development of energy storage. Its controllable surface morphology and adjustable pore structure have been widely used. It can be used not only as a precursor of silicon-carbon negative electrode for lithium-ion batteries, but also as a high-performance electrode material in supercapacitors. Supercapacitor energy storage is achieved by the adsorption / desorption of electrolyte ions on the surface of electrode materials to form a double layer. Therefore, the specific surface area and ionic conductivity of the material will greatly affect the performance of supercapacitor porous carbon materials. Moreover, the pore volume of the material will further affect the energy storage characteristics of porous carbon. Traditional porous carbon materials are bulk materials. Although bulk porous carbon materials are rich in pores, their rich micropores often exist in deep layers, which cannot effectively form a double layer to achieve energy storage and cannot give full play to the characteristics of high specific surface area of ​​the material. Nanomaterials are a new type of multidimensional material. The special microporous structure is constructed by morphology design methods to give full play to the excellent characteristics of high specific surface area of ​​porous carbon materials. It is a feasible solution to improve the performance of porous carbon electrode materials for supercapacitors. CN118762938A discloses a method for preparing a porous carbon material, which uses gallic acid as a precursor and magnesium salt as an activator, and obtains an activated carbon material after a simple ball milling, mixing and carbonization treatment. CN117954234A discloses a method for preparing a biomass-derived porous carbon material and its application, which uses biomass as a carbon source, mixes with potassium hydroxide and zinc acetate to obtain a slurry, and then performs a one-step carbonization and activation treatment to obtain a porous carbon material. The porous carbons obtained above are all bulk porous carbons, and their electrochemical properties do not match their high specific surface area, indicating that the pore utilization rate in the block is low and the excellent performance of the high specific surface area cannot be brought into play. Summary of the invention

[0003] The first purpose of the present invention is to provide a method for preparing porous carbon with a nanosheet shell-encapsulated porous skeleton structure, so as to solve practical problems such as low pore utilization and performance optimization barriers of existing bulk porous carbon materials.

[0004] The second object of the present invention is to provide a porous carbon with a porous skeleton structure wrapped in a nanosheet shell obtained by the above-mentioned preparation method, wherein the porous carbon with a porous skeleton structure wrapped in a nanosheet shell has the advantages of high specific surface area and high surface utilization rate.

[0005] The technical solution is as follows:

[0006] A method for preparing porous carbon with a nanosheet-shell-encapsulated porous skeleton structure, the method adopts molten salt catalytic activation to prepare the porous carbon with a nanosheet-shell-encapsulated porous skeleton structure; the method is characterized by comprising the following steps:

[0007] Step 1: crushing the mesocarbon microspheres by air flow milling, and then grading and screening to obtain finely screened mesocarbon microspheres, and controlling the uniformity of the particle size of the mesocarbon microspheres;

[0008] Step 2: uniformly mix the finely sieved mesocarbon microspheres and the Na2CO3 activator according to a mass ratio to obtain a mixed material;

[0009] Step 3: Place the mixed material from step 2 in a tubular furnace under an argon atmosphere, heat it to the water vaporization temperature at a certain heating rate to eliminate the influence of moisture, then heat it to the melting temperature at a certain heating rate to fully melt the Na2CO3 activator, and finally heat it to the activation temperature at a certain heating rate to perform an activation reaction, then cool it to room temperature and take it out;

[0010] This step 3 is the core invention of the present invention. By controlling the temperature of the Na2CO3 activator during the activation process, the preparation of porous carbon with a porous skeleton structure of nanosheet shells with mesophase carbon microspheres as precursors is achieved. The Na2CO3 activator and the decomposition product Na2O are used as templates. The reaction rate is controlled by designing the ratio of the Na2CO3 activator to the mesophase carbon microspheres. The liquid ion environment generated by the melting of the Na2CO3 activator cuts off the long molecular chains in the mesophase carbon microspheres, guides the long chains into rings, and finally reorganizes to form nanosheet shells. The internal agglomeration caused by the Na2CO3 activator forms a skeleton structure. This structure is rich in mesopores, which increases the electrolyte contact area of ​​the material in capacitor energy storage.

[0011] Step 4: Heat and stir the activated material with HCl solution to remove the remaining Na2CO3 activator, and wash with deionized water until the solution is neutral;

[0012] Step 5: Filter and dry the product obtained in step 4 to obtain the porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0013] Preferably, the particle size of the mesophase carbon microspheres after fine screening in step 1 is less than 10 μm. The pitch of the mesophase carbon microspheres will greatly affect the particle size of the porous carbon with a porous skeleton structure of nanosheet shells. Controlling the particle size of the mesophase carbon microspheres can better control the size of the activated product, the porous carbon with a porous skeleton structure of nanosheet shells. In addition, the particle size of the porous carbon will affect its performance as an active substance in the preparation of electrodes.

[0014] Preferably, the mass ratio of the mesocarbon microspheres to the Na2CO3 activator after fine screening in step 2 is 1:1-1:4. When Na2CO3 is used as an activator to react with the mesocarbon microspheres, the amount of the Na2CO3 activator added will affect the reaction rate of the mesocarbon microspheres. By designing different activation reaction processes with different ratios, the growth of porous carbon with a porous skeleton structure of nanosheet shells can be better controlled.

[0015] Preferably, step 3 further includes: the temperature for eliminating the influence of moisture is 110°C, the melting temperature of the Na2CO3 activator is 860°C, the activation temperature is 900°C-1000°C, the activation reaction time is 2-5h, wherein the heating rate is 5°C / min, and the activation reaction is naturally cooled to room temperature after completion. The mesophase carbon microspheres and the Na2CO3 activator contain a certain amount of moisture, which will not only affect the yield of porous carbon, but also affect the progress of the activation reaction. The melting point of the Na2CO3 activator is 851°C. Selecting 860°C as the melting temperature can fully melt the Na2CO3 activator, forming a molten liquid phase that can better contact with the mesophase carbon microspheres and prepare for subsequent activation reactions. The activation temperature is selected to be 900°C-1000°C. When the activation temperature is higher than 900°C, the Na in the molten state of the Na2CO3 activator + It will cut the carbon chain in the mesophase carbon microspheres and guide the carbon chain to rearrange to form nanosheet shells. When the activation temperature is higher than 1000℃, the excessively high temperature will cause the nanosheet shells to agglomerate, which is not conducive to capacitor energy storage.

[0016] Preferably, in step 4, the concentration of hydrochloric acid is 1 mol / L, and the stirring time is 5-8 hours. Impurities can affect the electrochemical properties of porous carbon, and the impurity content of porous carbon is controlled by washing with dilute hydrochloric acid to ensure the purity of porous carbon with nanosheet shell-wrapped porous skeleton structure.

[0017] Preferably, the product obtained in step 5 is placed in an oven at 120° C. and dried for 12-24 hours. The nanosheet shell-encapsulated porous skeleton structure porous carbon is placed in an oven and dried overnight to eliminate moisture in the material.

[0018] The invention discloses a porous carbon material with a nano-sheet shell-encapsulated porous skeleton structure, which is characterized in that the porous carbon with a nano-sheet shell-encapsulated porous skeleton structure is prepared by adopting molten salt catalytic activation.

[0019] The present invention also discloses a supercapacitor, which is characterized by comprising an electrode material, wherein the electrode material is the porous carbon with a porous skeleton structure wrapped in a nanosheet shell.

[0020] The present invention also discloses an electrode, which is characterized by: mixing the prepared nanosheet shell-coated porous skeleton structure porous carbon material, acetylene black, and polytetrafluoroethylene binder in a mass ratio of 8:1:1, adding deionized water dropwise, mixing, pressing into sheets, extruding onto foamed nickel, and placing in a 120°C vacuum drying oven for drying overnight.

[0021] The present invention also discloses a test method for testing the electrochemical performance of an electrode, which is a test method for testing the above-mentioned electrode; the electrode electrochemical performance test is carried out using a three-electrode system, using a 6M KOH solution as an electrolyte, a platinum sheet electrode as a counter electrode, and a mercuric oxide electrode as a reference electrode.

[0022] The invention also discloses a porous carbon with a nano-sheet shell-encapsulated porous skeleton structure, which is characterized in that the porous carbon with a nano-sheet shell-encapsulated porous skeleton structure is prepared by the above method.

[0023] Preferably, the nanosheet-shell porous carbon with porous skeleton structure includes a large number of micropores and mesopores, and the pore size distribution of the micropores and mesopores is relatively uniform; -1 At a current density of 1.34 W / m, the discharge capacity in aqueous alkaline electrolyte is 124 F g -1 .

[0024] Beneficial Effects

[0025] 1. Using mesophase carbon microspheres as raw materials, a simple, green, environmentally friendly, and large-scale preparation method was adopted to prepare porous carbon with a nanosheet shell-encapsulated porous skeleton structure.

[0026] 2. The preparation method of porous carbon with porous skeleton structure of nano-sheet shell provided by the present invention is to use mesophase carbon microspheres as raw materials, adopt Na2CO3 as template and activator, utilize the characteristics that Na2CO3 decomposes and melts at a certain temperature and the decomposition product Na2O does not melt, and prepare this porous carbon with special structure through a certain activation environment design. Specifically, Na2CO3 begins to decompose when it reaches its melting point, generating Na2O and CO2 gas, and at the same time, the excess Na2CO3 will form a molten state, and this molten liquid phase state will make the contact between the activator and the mesophase carbon microspheres more sufficient, thereby guiding the carbon microspheres to agglomerate. As the temperature rises, the Na2O generated by the decomposition of part of Na2CO3 remains inside and outside the agglomerate. Since the temperature does not reach the melting point of Na2O, the internal Na2O will act as a template in the agglomerate, thereby removing the pores in the subsequent treatment. As the temperature rises further, the CO2 produced will react with the carbon microspheres, a process involving gas activation. At the same time, the external Na2O will further react with the gas activation product CO to generate nanosheets and reorganize into shells.

[0027] 3. The porous carbon with a porous skeleton structure coated with nanosheets has a rich porous structure and a special microscopic morphology, which is beneficial to the storage of electrolyte ions and the surface adsorption and desorption reaction. The present invention can obtain a porous carbon with a porous skeleton structure coated with nanosheets at a relatively low activation temperature, which has a high specific surface area, high electrical conductivity and high tap density and can be used as a supercapacitor electrode material with very good capacitance performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of the porous carbon with a nanosheet shell-encapsulated porous skeleton structure prepared in Example 1.

[0029] Figure 2 This is a transmission electron micrograph of the porous carbon with a nanosheet shell-encapsulated porous skeleton structure prepared in Example 1.

[0030] Figure 3 This is the electrochemical performance diagram of the porous carbon with a porous skeleton structure encapsulated by nanosheets prepared in Example 1.

[0031] Figure 4 This is the isothermal adsorption diagram of the porous carbon with a porous skeleton structure encapsulated by nanosheets prepared in Example 1.

[0032] Figure 5 This is the pore size distribution diagram of the porous carbon with nanosheet shell-encapsulated porous skeleton structure prepared in Example 1. DETAILED DESCRIPTION

[0033] The embodiments of the present invention will be described in detail below in conjunction with examples, but those skilled in the art will understand that the following examples are only used for the present invention and should not be regarded as limiting the scope of the present invention. The present invention will be further described below in conjunction with the accompanying drawings and examples.

[0034] A method for preparing porous carbon with a nanosheet-shell-encapsulated porous skeleton structure, the method adopts molten salt catalytic activation to prepare the porous carbon with a nanosheet-shell-encapsulated porous skeleton structure; the method is characterized by comprising the following steps:

[0035] Step 1: crushing the mesocarbon microspheres by air flow milling, and then grading and screening to obtain finely screened mesocarbon microspheres, and controlling the uniformity of the particle size of the mesocarbon microspheres;

[0036] Step 2: uniformly mix the finely sieved mesocarbon microspheres and the Na2CO3 activator according to a mass ratio to obtain a mixed material;

[0037] Step 3: Place the mixed material from step 2 in a tubular furnace under an argon atmosphere, heat it to the water vaporization temperature at a certain heating rate to eliminate the influence of moisture, then heat it to the melting temperature at a certain heating rate to fully melt the Na2CO3 activator, and finally heat it to the activation temperature at a certain heating rate to perform an activation reaction, then cool it to room temperature and take it out;

[0038] Step 4: Heat and stir the activated material with HCl solution to remove the remaining Na2CO3 activator, and wash with deionized water until the solution is neutral;

[0039] Step 5: Filter and dry the product obtained in step 4 to obtain the porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0040] Example 1

[0041] (1) Weigh 100 g of mesocarbon microspheres and place them in a jet mill for 15 min. After passing through a fine sieve, the particles have a particle size of less than 10 μm.

[0042] (2) The finely sieved medium-temperature asphalt and the Na2CO3 activator are uniformly mixed in a mass ratio of 1:4, and 10 g of mesophase carbon microbeads and 40 g of Na2CO3 are taken.

[0043] (3) The mixed material is placed in a tubular furnace with an argon atmosphere for activator melting and activation. The temperature is raised to 110°C and kept for 30 minutes to eliminate the influence of moisture. The melting temperature of the Na2CO3 activator is 860°C, the holding time is 0.5h, the activation temperature is 950°C, and the activation time is 5h. The heating rate is 5°C / min. After activation, it is naturally cooled to room temperature.

[0044] (4) The activated material was washed with 1 mol / L HCl solution and deionized water until the solution became neutral. Finally, the material was placed in a freeze dryer for freeze drying for 12 h to obtain a porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0045] (5) Preparation of electrode materials. The prepared nanosheet shell-coated porous carbon with porous skeleton structure, acetylene black and polytetrafluoroethylene binder are mixed in a mass ratio of 8:1:1, deionized water is added and the mixture is pressed into sheets and squeezed onto nickel foam. The sheets are placed in a vacuum drying oven at 120°C and dried overnight. (6) The electrochemical performance test of the obtained material is carried out using a three-electrode system, with 6MKOH solution as the electrolyte, platinum sheet as the counter electrode, and mercuric oxide electrode as the reference electrode. The cyclic voltammetry test, impedance test and constant current charge and discharge performance test are carried out using a Chenhua electrochemical workstation. The cyclic voltammetry test is set up with a voltage range of -1V to 0V and a scan rate of 10mV s -1; Impedance test setting, frequency range is 100KHz-0.01Hz, voltage is initial open circuit voltage; Constant current charge and discharge performance test setting, voltage range is -1V to 0V, current density is 1A -1 .

[0046] The porous carbon with a nanosheet-shell-encapsulated porous skeleton structure obtained in Example 1 is shown in the accompanying drawings, wherein: Figure 1 The scanning electron microscope shows the porous carbon with a porous skeleton structure wrapped by nanosheet shells. It can be seen that the prepared material is a porous carbon composed of nanosheet shells and an internal porous skeleton structure.

[0047] Figure 2 This is a transmission electron microscope image of porous carbon with a porous skeleton structure wrapped in nanosheets. It can be clearly seen that the prepared material has a porous skeleton inside and is assembled from two-dimensional nanosheets outside.

[0048] Figure 3 The three-electrode constant current charge-discharge curve of the porous carbon with porous skeleton structure wrapped in nanosheet shell is shown. -1 At a current density of 1.24 F g -1 .

[0049] Figure 4 The isothermal adsorption curve of the prepared porous carbon with a porous skeleton structure is shown in Figure 2. The isothermal adsorption and desorption test results show that the specific surface area of ​​the material is 1451m 2 g -1 From the figure, we can see that the sample has a type IV isotherm curve, indicating that the sample has a large number of micropores and mesopores, proving that the material is a porous structure.

[0050] Figure 5 The pore size distribution diagram of the prepared porous carbon with a nanosheet shell-encapsulated porous skeleton structure is shown. The pore size distribution results show that the micropores of the material are uniformly distributed in the range of 1.12-1.64 nm, while the mesopores are uniformly distributed between 2.78-4.26 nm.

[0051] Example 2

[0052] (1) Weigh 100 g of mesocarbon microspheres and place them in a jet mill for 15 min. After passing through a fine sieve, the particles have a particle size of less than 10 μm.

[0053] (2) The finely sieved medium-temperature asphalt and the Na2CO3 activator are uniformly mixed in a mass ratio of 1:4, and 10 g of mesophase carbon microbeads and 40 g of Na2CO3 are taken.

[0054] (3) The mixed material is placed in a tubular furnace with an argon atmosphere for activator melting and activation. The temperature is raised to 110°C and kept for 30 minutes to eliminate the influence of moisture. The melting temperature of the Na2CO3 activator is 800°C, the holding time is 0.5h, the activation temperature is 950°C, and the activation time is 5h. The heating rate is 5°C / min. After activation, it is naturally cooled to room temperature.

[0055] (4) The activated material was washed with 1 mol / L HCl solution and deionized water until the solution became neutral. Finally, the material was placed in a freeze dryer for freeze drying for 12 h to obtain a porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0056] The porous carbon obtained by the above-mentioned embodiment is analyzed to have a low melting temperature, the activator is not fully melted to contact with the mesophase carbon microspheres, and no special morphology structure is obtained.

[0057] Example 3

[0058] (1) Weigh 100 g of mesocarbon microspheres and place them in a jet mill for 15 min. After passing through a fine sieve, the particles have a particle size of less than 10 μm.

[0059] (2) The finely sieved medium-temperature asphalt and the Na2CO3 activator are uniformly mixed in a mass ratio of 1:4, and 10 g of mesophase carbon microbeads and 40 g of Na2CO3 are taken.

[0060] (3) The mixed material is placed in a tubular furnace with an argon atmosphere for activator melting and activation. The temperature is raised to 110°C and kept for 30 minutes to eliminate the influence of moisture. The melting temperature of the Na2CO3 activator is 860°C, the holding time is 2 hours, the activation temperature is 950°C, and the activation time is 5 hours. The heating rate is 5°C / min. After activation, it is naturally cooled to room temperature.

[0061] (4) The activated material was washed with 1 mol / L HCl solution and deionized water until the solution became neutral. Finally, the material was placed in a freeze dryer for freeze drying for 12 h to obtain a porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0062] The porous carbon obtained by the above-mentioned embodiment is analyzed to know that: the melting time of the activator is too long, resulting in a large amount of decomposition of the activator, and there is no sufficient contact and reaction with the mesophase carbon microspheres, and the special morphology structure cannot be obtained.

[0063] Example 4

[0064] (1) Weigh 100 g of mesocarbon microspheres and place them in a jet mill for 15 min. After passing through a fine sieve, the particles have a particle size of less than 10 μm.

[0065] (2) The finely sieved medium-temperature asphalt and the Na2CO3 activator are uniformly mixed in a mass ratio of 1:2, and 10 g of mesophase carbon microbeads and 20 g of Na2CO3 are taken.

[0066] (3) The mixed material is placed in a tubular furnace with an argon atmosphere for activator melting and activation. The temperature is raised to 110°C and kept for 30 minutes to eliminate the influence of moisture. The melting temperature of the Na2CO3 activator is 860°C, the holding time is 0.5h, the activation temperature is 950°C, and the activation time is 5h. The heating rate is 5°C / min. After activation, it is naturally cooled to room temperature.

[0067] (4) The activated material was washed with 1 mol / L HCl solution and deionized water until the solution became neutral. Finally, the material was placed in a freeze dryer for freeze drying for 12 h to obtain a porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0068] The porous carbon obtained through the above-mentioned examples is analyzed to know that: the amount of activator used is too small to fully react with the relatively large number of mesophase carbon microspheres, and a porous carbon material with a special morphology and structure cannot be obtained.

[0069] Example 5

[0070] (1) Weigh 100 g of mesocarbon microspheres and place them in a jet mill for 15 min. After passing through a fine sieve, the particles have a particle size of less than 10 μm.

[0071] (2) The finely sieved medium-temperature asphalt and the Na2CO3 activator are uniformly mixed in a mass ratio of 1:4. Take 10g of the finely sieved medium-temperature asphalt and 40g of Na2CO3.

[0072] (3) The mixed material is placed in a tubular furnace with an argon atmosphere for activator melting and activation. The temperature is raised to 110°C and kept warm for 30 minutes to eliminate the influence of moisture. The melting temperature of the Na2CO3 activator is 860°C, the holding time is 0.5h, the activation temperature is 1100°C, and the activation time is 5h. The heating rate is 5°C / min. After activation, it is naturally cooled to room temperature.

[0073] (4) The activated material was washed with 1 mol / L HCl solution and deionized water until the solution became neutral. Finally, the material was placed in a freeze dryer for freeze drying for 12 h to obtain a porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

[0074] The porous carbon materials obtained by the above examples are analyzed and found to be: too high activation temperature causes the decomposition products of the activator to melt, inhibiting the catalytic properties of the decomposition products, destroying the original nanosheet shell structure growth, and failing to form porous carbon materials with special morphology. The porous carbons with nanosheet shell-encapsulated porous skeleton structures obtained by testing examples 1-5 are shown in Table 1:

[0075] Table 1

[0076]

[0077] As can be seen from Table 1, the method for preparing porous carbon with a nanosheet-shell-encapsulated porous skeleton structure by molten salt catalytic activation provided by the present invention can obtain a porous carbon with a nanosheet-shell-encapsulated porous skeleton structure having a high specific surface area, a high tap density and a special morphology. The porous carbon with a nanosheet-shell-encapsulated porous skeleton structure obtained by the scheme of Example 1 has a high specific surface area and a large tap density, and has better capacitance performance as a supercapacitor carbon.

[0078] The above is a detailed introduction to the preparation method of porous carbon with a porous skeleton structure coated with nanosheets provided by the present invention. The present invention introduces a method of melting an activator, so that sodium carbonate is used as a mild activator to melt at a relatively low temperature to guide the mesophase carbon microspheres to agglomerate into a skeleton, and at the same time, the decomposition products are catalytically converted into nanosheet "eggshells" at a relatively high temperature, ultimately forming porous carbon with a porous skeleton structure coated with nanosheets.

[0079] Finally, it should be noted that the above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing porous carbon with a nanosheet-shell-encapsulated porous skeleton structure, the method adopts molten salt catalytic activation to prepare porous carbon with a nanosheet-shell-encapsulated porous skeleton structure; the method is characterized by: The steps include: Step 1: crushing the mesocarbon microspheres by air flow milling, and then grading and screening to obtain finely screened mesocarbon microspheres, and controlling the uniformity of the particle size of the mesocarbon microspheres; Step 2: uniformly mix the finely sieved mesocarbon microspheres and the Na2CO3 activator according to a mass ratio to obtain a mixed material; Step 3: Place the mixed material from step 2 in a tubular furnace under an argon atmosphere, heat it to the water vaporization temperature at a certain heating rate to eliminate the influence of moisture, then heat it to the melting temperature at a certain heating rate to fully melt the Na2CO3 activator, and finally heat it to the activation temperature at a certain heating rate to perform an activation reaction, then cool it to room temperature and take it out; Step 4: Heat and stir the activated material with HCl solution to remove the remaining Na2CO3 activator, and wash with deionized water until the solution is neutral; Step 5: Filter and dry the product obtained in step 4 to obtain the porous carbon with a nanosheet-shell-encapsulated porous skeleton structure.

2. The method for preparing porous carbon with nanosheet shell-encapsulated porous skeleton structure according to claim 1, characterized in that: The particle size of the mesocarbon microspheres in step 1 is less than 20 μm.

3. The method for preparing porous carbon with nanosheet shell-encapsulated porous skeleton structure according to claim 1, characterized in that: The step 2 further comprises: the mass ratio of the finely screened mesocarbon microspheres to the Na2CO3 activator is 1:1-1:

4.

4. The method for preparing porous carbon with nanosheet shell-encapsulated porous skeleton structure according to claim 1, characterized in that: The step 3 further includes: the water vaporization temperature for eliminating the influence of moisture is 110°C, the heating rate is 5°C / min, the insulation time is 30min, the melting temperature of the Na2CO3 activator is 860°C, the heating rate is 5°C / min, the melting time is 2h, the activation temperature is 900°C-1000°C, the heating rate is 5°C / min, the activation reaction time is 2-5h, and the activation reaction is naturally cooled to room temperature after the activation reaction is completed.

5. The method for preparing porous carbon with nanosheet shell-encapsulated porous skeleton structure according to claim 1, characterized in that: In step 5, the concentration of hydrochloric acid is 1 mol / L, and the stirring time is 5-8 hours.

6. The method for preparing porous carbon with nanosheet shell-encapsulated porous skeleton structure according to claim 1, characterized in that: The product obtained in step 6 is placed in an oven and dried for 12-24 hours.

7. A porous carbon material with a porous skeleton structure encapsulated by nanosheets, characterized in that the porous carbon material with a porous skeleton structure encapsulated by nanosheets is prepared by the method for preparing the porous carbon with a porous skeleton structure encapsulated by nanosheets according to any one of claims 1 to 6.

8. The porous carbon material with a nanosheet-shell-encapsulated porous skeleton structure according to claim 7 is characterized in that: the porous carbon material comprises a large number of micropores and mesopores, and the pore sizes of the micropores and mesopores are uniformly distributed; -1 At a current density of 1.34 W / m, the discharge capacity in aqueous alkaline electrolyte is 124 F g -1 .

9. An electrode; characterized in that: The porous carbon material with a porous skeleton structure of nanosheet shells as claimed in claim 7 is mixed with acetylene black and polytetrafluoroethylene binder in a mass ratio of 8:1:1, deionized water is added dropwise, the mixture is pressed into a sheet shape, extruded onto nickel foam, and dried overnight in a vacuum drying oven at 120°C.

10. A test method for testing the electrochemical performance of an electrode, the test method is a test method for testing the electrode described in claim 9; the electrode electrochemical performance test is carried out using a three-electrode system, using a 6M KOH solution as an electrolyte, a platinum sheet electrode as a counter electrode, and a mercuric oxide electrode as a reference electrode.

Citation Information

Patent Citations

  • Biomass-derived porous carbon material as well as preparation method and application thereof

    CN117954234A

  • Porous carbon material as well as preparation method and application thereof

    CN118762938A